PENGARUH PROMOSI MEDIA SOSIAL DAN KUALITAS WEBSITE TERHADAP KEPUTUSAN SISWA MEMILIH LEMBAGA BIMBINGAN BELAJAR ENGLISH FOR SKILL KAMPUNG INGGRIS PARE - Chozin Ary Wicaksono; Sri Wahyuni Mega Hastuti; Sumarji Sumarji (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
Digital promotion is becoming more effective promotion strategy for companies because it is considered more targeted and communicative, that case also happen in English courses in Kampung Inggris Pare, which is starting to move from traditional promotion strategies to digital marketing especially in social media promotion and using website as information provider. The purpose of this study are (1) testing the significance of the social media promotion effect on student’s decision to choose EFS English course (2) testing the significance of the website quality effect on students' decisions to choose EFS English course (3) testing determine the significance of social media promotion and website quality simultaneously on student’s decision to choose EFS English course. This type of research is quantitative research using multiple linear regression. This research was conducted at English for Skill Pare with sample of 66 students. The results of this study are (1) Social media promotion has significant effect on the student’s decision to choose EFS English course (2) Website quality has significant effect on the student's decision to choose EFS English course (3) Simultaneously social media promotion and website quality have positive and significant effect on the student's decision to choose EFS English course.